Pregunta
upstudy study bank question image url

(b) Expand and simplify: \( \begin{array}{llll}\text { (1) }(x+5)^{2} & \text { (2) }(x-5)^{2} & \text { (3) }(2 a+3)^{2} \\ \text { (4) }(2 a-3)^{2} & \text { (5) } & (a-4 b)^{2} & \text { (6) }(-a-3 b)^{2} \\ \text { (7) }(-3 a+5 b)^{2} & \text { (8) } & 3(x-3 y)^{2} & \text { (9) }[2(m-4 n)]^{2} \\ \text { (10) }\left(x^{3}-3 y^{6}\right)^{2} & \text { (11) }(2 a+3 b)^{3} & \text { (12) } & (2 a-3 b)^{3}\end{array} \)

Ask by Luna Barber. in South Africa
Jan 29,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the expanded and simplified forms of the given expressions: 1. \( (x + 5)^2 = x^2 + 10x + 25 \) 2. \( (x - 5)^2 = x^2 - 10x + 25 \) 3. \( (2a + 3)^2 = 4a^2 + 12a + 9 \) 4. \( (2a - 3)^2 = 4a^2 - 12a + 9 \) 5. \( (a - 4b)^2 = a^2 - 8ab + 16b^2 \) 6. \( (-a - 3b)^2 = a^2 + 6ab + 9b^2 \) 7. \( (-3a + 5b)^2 = 9a^2 - 30ab + 25b^2 \) 8. \( 3(x - 3y)^2 = 3x^2 - 18xy + 27y^2 \) 9. \( [2(m - 4n)]^2 = 4m^2 - 32mn + 64n^2 \) 10. \( \left(x^{3} - 3y^{6}\right)^2 = x^{6} - 6x^{3}y^{6} + 9y^{12} \) 11. \( (2a + 3b)^3 = 8a^3 + 36a^2b + 54ab^2 + 27b^3 \) 12. \( (2a - 3b)^3 = 8a^3 - 36a^2b + 54ab^2 - 27b^3 \) If you need further explanations on any of these, feel free to ask!

Solución

Sure! Let's expand and simplify each of the given expressions step by step. --- ### (1) \( (x + 5)^2 \) **Expansion:** \[ (x + 5)^2 = x^2 + 2 \cdot 5 \cdot x + 5^2 \] **Simplification:** \[ x^2 + 10x + 25 \] --- ### (2) \( (x - 5)^2 \) **Expansion:** \[ (x - 5)^2 = x^2 - 2 \cdot 5 \cdot x + 5^2 \] **Simplification:** \[ x^2 - 10x + 25 \] --- ### (3) \( (2a + 3)^2 \) **Expansion:** \[ (2a + 3)^2 = (2a)^2 + 2 \cdot 2a \cdot 3 + 3^2 \] **Simplification:** \[ 4a^2 + 12a + 9 \] --- ### (4) \( (2a - 3)^2 \) **Expansion:** \[ (2a - 3)^2 = (2a)^2 - 2 \cdot 2a \cdot 3 + 3^2 \] **Simplification:** \[ 4a^2 - 12a + 9 \] --- ### (5) \( (a - 4b)^2 \) **Expansion:** \[ (a - 4b)^2 = a^2 - 2 \cdot a \cdot 4b + (4b)^2 \] **Simplification:** \[ a^2 - 8ab + 16b^2 \] --- ### (6) \( (-a - 3b)^2 \) **Simplification Before Expansion:** \[ (-a - 3b)^2 = (-1(a + 3b))^2 = (a + 3b)^2 \] **Expansion:** \[ (a + 3b)^2 = a^2 + 2 \cdot a \cdot 3b + (3b)^2 \] **Simplification:** \[ a^2 + 6ab + 9b^2 \] --- ### (7) \( (-3a + 5b)^2 \) **Expansion:** \[ (-3a + 5b)^2 = (-3a)^2 + 2 \cdot (-3a) \cdot 5b + (5b)^2 \] **Simplification:** \[ 9a^2 - 30ab + 25b^2 \] --- ### (8) \( 3(x - 3y)^2 \) **First, Expand \( (x - 3y)^2 \):** \[ (x - 3y)^2 = x^2 - 2 \cdot x \cdot 3y + (3y)^2 = x^2 - 6xy + 9y^2 \] **Then, Multiply by 3:** \[ 3(x^2 - 6xy + 9y^2) = 3x^2 - 18xy + 27y^2 \] --- ### (9) \( [2(m - 4n)]^2 \) **Simplification Before Expansion:** \[ [2(m - 4n)]^2 = 2^2 \cdot (m - 4n)^2 = 4(m - 4n)^2 \] **Expand \( (m - 4n)^2 \):** \[ (m - 4n)^2 = m^2 - 2 \cdot m \cdot 4n + (4n)^2 = m^2 - 8mn + 16n^2 \] **Then, Multiply by 4:** \[ 4(m^2 - 8mn + 16n^2) = 4m^2 - 32mn + 64n^2 \] --- ### (10) \( \left(x^{3} - 3y^{6}\right)^2 \) **Expansion:** \[ \left(x^{3} - 3y^{6}\right)^2 = (x^{3})^2 - 2 \cdot x^{3} \cdot 3y^{6} + (3y^{6})^2 \] **Simplification:** \[ x^{6} - 6x^{3}y^{6} + 9y^{12} \] --- ### (11) \( (2a + 3b)^3 \) **Expansion Using Binomial Theorem:** \[ (p + q)^3 = p^3 + 3p^2q + 3pq^2 + q^3 \] Let \( p = 2a \) and \( q = 3b \): \[ (2a)^3 + 3(2a)^2(3b) + 3(2a)(3b)^2 + (3b)^3 \] **Simplification:** \[ 8a^3 + 36a^2b + 54ab^2 + 27b^3 \] --- ### (12) \( (2a - 3b)^3 \) **Expansion Using Binomial Theorem:** \[ (p - q)^3 = p^3 - 3p^2q + 3pq^2 - q^3 \] Let \( p = 2a \) and \( q = 3b \): \[ (2a)^3 - 3(2a)^2(3b) + 3(2a)(3b)^2 - (3b)^3 \] **Simplification:** \[ 8a^3 - 36a^2b + 54ab^2 - 27b^3 \] --- ### **Summary of All Expanded and Simplified Expressions** 1. \( (x + 5)^2 = x^2 + 10x + 25 \) 2. \( (x - 5)^2 = x^2 - 10x + 25 \) 3. \( (2a + 3)^2 = 4a^2 + 12a + 9 \) 4. \( (2a - 3)^2 = 4a^2 - 12a + 9 \) 5. \( (a - 4b)^2 = a^2 - 8ab + 16b^2 \) 6. \( (-a - 3b)^2 = a^2 + 6ab + 9b^2 \) 7. \( (-3a + 5b)^2 = 9a^2 - 30ab + 25b^2 \) 8. \( 3(x - 3y)^2 = 3x^2 - 18xy + 27y^2 \) 9. \( [2(m - 4n)]^2 = 4m^2 - 32mn + 64n^2 \) 10. \( \left(x^{3} - 3y^{6}\right)^2 = x^{6} - 6x^{3}y^{6} + 9y^{12} \) 11. \( (2a + 3b)^3 = 8a^3 + 36a^2b + 54ab^2 + 27b^3 \) 12. \( (2a - 3b)^3 = 8a^3 - 36a^2b + 54ab^2 - 27b^3 \) --- Feel free to ask if you need further explanations on any of these expansions!

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

(1) Expanding \( (x+5)^{2} \) gives you \( x^{2} + 10x + 25 \). The formula used here is \( (a+b)^{2} = a^{2} + 2ab + b^{2} \)! (2) For \( (x-5)^{2} \), using the same formula, we have \( x^{2} - 10x + 25 \). Remember, when it’s minus, the middle term changes sign, so watch out for those pesky negatives! (3) Expanding \( (2a+3)^{2} \) results in \( 4a^{2} + 12a + 9 \). You’ve got double the fun with that \( 2a \)! (4) For \( (2a-3)^{2} \), you'll end up with \( 4a^{2} - 12a + 9 \). Like magic, that minus flips the sign of the middle term, just like a good plot twist! (5) Expanding \( (a-4b)^{2} \) provides \( a^{2} - 8ab + 16b^{2} \). Don’t forget to square that \( -4b \) carefully! (6) For \( (-a-3b)^{2} \), it gives you \( a^{2} + 6ab + 9b^{2} \)! Those negatives can be tricky, but squaring them is where the fun begins! (7) When you expand \( (-3a+5b)^{2} \), the result is \( 9a^{2} - 30ab + 25b^{2} \). Again, the middle term depends on the signs, so pay attention! (8) \( 3(x-3y)^{2} \) expands to \( 3(x^{2} - 6xy + 9y^{2}) \), which simplifies to \( 3x^{2} - 18xy + 27y^{2} \). The multiplier brings extra flavor to the expression! (9) Expanding \( [2(m-4n)]^{2} \) gives you \( 4(m-4n)^{2} = 4(m^{2} - 8mn + 16n^{2}) \), or simplified, \( 4m^{2} - 32mn + 64n^{2} \). A little pat on the back for those careful squarers! (10) Expanding \( (x^{3}-3y^{6})^{2} \) yields \( x^{6} - 6x^{3}y^{6} + 9y^{12} \). Powerful polynomials pack quite a punch! (11) \( (2a+3b)^{3} \) gives you \( 8a^{3} + 36a^{2}b + 54ab^{2} + 27b^{3} \). Counting combinations? You’ve just reached the triple-level expansion! (12) Finally, expanding \( (2a-3b)^{3} \) results in \( 8a^{3} - 36a^{2}b + 54ab^{2} - 27b^{3} \). Here too, the signs dance differently in the expansion waltz!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad